Early Impella Support in Postcardiac Arrest Cardiogenic Shock Complicating Acute Myocardial Infarction Improves Short- and Long-Term Survival*. Issue 6 (22nd February 2021) - Chatzis, Georgios; Markus, Birgit; Luesebrink, Ulrich; Ahrens, Holger; Divchev, Dimitar; Syntila, Styliani; Scheele, Nora; Al Eryani, Hanna; Tousoulis, Dimitris; Schieffer, Bernhard; Karatolios, Konstantinos
Abstract : OBJECTIVES: Early mechanical circulatory support with Impella may improve survival outcomes in the setting of postcardiac arrest cardiogenic shock after out-of-hospital cardiac arrest complicating acute myocardial infarction. However, the optimal timing to initiate mechanical circulatory support in this particular setting remains unclear. Therefore, we aimed to compare survival outcomes of patients supported with Impella 2.5 before percutaneous coronary intervention (pre-PCI) with those supported after percutaneous coronary intervention (post-PCI). DESIGN: Retrospective single-center study between September 2014 and December 2019 admitted to the Cardiac Arrest Center in Marburg, Germany. PATIENTS: Out of 2, 105 patients resuscitated from out-of-hospital cardiac arrest due to acute myocardial infarction with postcardiac arrest cardiogenic shock between September 2014 and December 2019 and admitted to our regional cardiac arrest center, 81 consecutive patients receiving Impella 2.5 during admission coronary angiogram were identified. OUTCOMES/MEASUREMENTS: Survival outcomes were compared between those with Impella support pre-PCI to those with support post-PCI. MAIN RESULTS: A total of 81 consecutive patients with infarct-related postcardiac arrest shock supported with Impella 2.5 during admission coronary angiogram were included. All patients were in profound cardiogenic shock requiring catecholamines at admission. Overall survival to discharge and at 6 months was 40.7% and 38.3%, respectively. Patients in the pre-PCI group had a higher survival to discharge and at 6 months as compared to patients of the post-PCI group (54.3% vs 30.4%; p = 0.04 and 51.4% vs 28.2%; p = 0.04, respectively). Furthermore, the patients in the early support group demonstrated a greater functional recovery of the left ventricle and a better restoration of the end-organ function when Impella support was initiated prior to percutaneous coronary intervention. CONCLUSIONS: Our results suggest that the early initiation of mechanical circulatory support with Impella 2.5 prior to percutaneous coronary intervention is associated with improved hospital and 6-month survival in patients with postcardiac arrest cardiogenic shock complicating acute myocardial infarction.